Structural Exchange Rate Modeling: The Case of a Small Open Economy - Anton Kuzmin (Risks)
A new mathematical structural model of the exchange rate and a new nonlinear multifactorial dependence of the exchange rate dynamics on a wide system of fundamental economic factors are the main results of the work. The model includes a wide system of economic factors based on the balance of payments. The proposed mathematical modeling methodology (International Flows Equilibrium Exchange Rate; IFEER) makes it possible to include additional fundamental factors in the model. This is the main theoretical achievement of this study, which also has a clear practical application. The constructed model made it possible to reveal the mechanism and structure of dynamic pricing of the exchange rate from updated and improved positions. The period of the last completed major financial and economic crisis in recent Russian history was chosen for conducting empirical research. During the period under review, the proposed model (applied to the dynamics of the Russian ruble against the US dollar exchange rate) showed its sufficiently high practical applicability, which is confirmed by the calculated quality indicators.